Endogenous dipeptidyl peptidase IV modulates skeletal muscle arteriolar diameter in rats. Issue 2 (22nd January 2018) - Neidert, Leslie E.; Al‐Tarhuni, Mohammed; Goldman, Daniel; Kluess, Heidi A.; Jackson, Dwayne N.
Abstract: The purpose of this study is to investigate that dipeptidyl peptidase IV (DPP‐IV) released from skeletal and vascular smooth muscle can increase arteriolar diameter in a skeletal muscle vascular bed by reducing neuropeptide Y (NPY)‐mediated vasoconstriction. We hypothesized that the effect of myokine DPP‐IV would be greatest in the smallest and least in the largest arterioles. Eight male Sprague Dawley rats (age 7–9 weeks; mass, mean ± SD: 258 ± 41 g) were anesthetized and the gluteus maximus dissected in situ for intravital microscopy analysis of arteriolar diameter of the vascular network. Computational modeling was performed on the diameter measurements to evaluate the overall impact of diameter changes on network resistance and flow distribution. In the first set of experiments, whey protein isolate powder was added to physiological saline solution, put in a heated reservoir, and applied to the preparation to induce release of DPP‐IV from the muscle. This resulted in an order‐dependent increase in arteriolar diameter, with the largest change in the 6A arterioles (63% more reactive than 1A arterioles; P < 0.05). This effect was abolished by adding the DPP‐IV inhibitor, Diprotin A. To test if the DPP‐IV released was affecting NPY‐mediated vasoconstriction, we applied NPY and whey protein, which resulted in attenuated vasoconstriction. These findings suggest that DPP‐IV is released from muscle and has a unique effect on blood flow, which appears to act on NPY to attenuate vasoconstriction. The findings suggest that DPP‐IV released from the skeletal or smooth muscle can alter muscle blood flow. Abstract : We demonstrated that whey protein increases muscle released DPP‐IV. When whey protein is applied with exogenous NPY, the constriction is attenuated. This attenuation is abolished by adding a DPP‐IV inhibitor. This effect is greatest in distal arterioles and has a large effect on simulated muscle blood flow.